(untitled) (Current Horticulture, 2024)
The experiment was conducted on 10-year-old almond (Prunus dulcis. Mill) cultivar Pranyaj planted at 4m × 4m spacing at ICAR-Central Institute of Temperate Horticulture, Srinagar, Jammu and Kashmir, during 2013-14. The plants were received uniform cultural practices and grouped into eight categories on the basis of trunk cross sectional area (TCSA) of trees. The maximum canopy volume (30.45 m3), nut number (1340), nut yield (3.95 kg/ tree and 2.46 tonnes/ha), and leaf NPK content (2.31, 0.18, 1.75%) were recorded with highest TCSA (114.96 cm2). The nut weight (3.32g) and productivity efficiency (37.57cm2) were registered with minimum TCSA (82.25cm2). The positive correlation were obtained between TCSA and canopy volume, nut number, nut yield and leaf NPK content. Similarly, there was negative correlation between TCSA and nut weight and productivity efficiency in almond cultivar Pranyaj.